Stochastic Graph Transformation with Regions - Torrini, Paolo; Heckel, Reiko; Rath, Istvan; Bergmann, Gabor (Electronic Communications of the EASST, 2010)
Graph transformation can be used to implement stochastic simulation of dynamic systems based on semi-Markov processes, extending the standard approach based on Markov chains. The result is a discrete event system, where states are graphs, and events are rule matches associated to general distributions, rather than just exponential ones. We present an extension of this model, by introducing a hierarchical notion of event location, allowing for stochastic dependence of higher-level events on lower-level ones.